Effect of Storage Methods and Periods on the Nutritional Properties of Watermelon - Nishonova Asal Yakubjonovna; Juraev Urol Chorievich; Mokhinur Khasanova; Zokirov Kurbonalijon Gaybullo ogli (Zien Journals, 2022)
the article presents the results of research on changes in fruit quality and chemical composition when fruits of watermelon varieties and hybrids are stored in a combined method (in the open field and in a naturally ventilated warehouse). Also in the article, the advantages of this storage method are explained from a scientific point of view.
Keywords: aromatic substances; field; naturally ventilated warehouse; drip irrigation